2019
DOI: 10.1016/j.clnu.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Diamine oxidase (DAO) supplement reduces headache in episodic migraine patients with DAO deficiency: A randomized double-blind trial

Abstract: ISRCTN10091019; www.isrctn.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…However, these drugs have several side effects [7]. Hence, several supplementary treatments have been suggested for the management of migraine symptoms [8][9][10][11]. Among these methods, supplementation with some micronutrients receives a great deal of attention [2,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs have several side effects [7]. Hence, several supplementary treatments have been suggested for the management of migraine symptoms [8][9][10][11]. Among these methods, supplementation with some micronutrients receives a great deal of attention [2,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of exogenous porcine DAO to support the endogenous DAO in the human intestine is claimed to reduce histamine‐associated physiological symptoms (Izquierdo‐Casas et al., 2019; Komericki et al., 2011; Schnedl et al., 2019; Yacoub et al., 2018). However, we showed in our histamine reduction experiments that the DAO activity required for a satisfactory supplementation is considerably higher than expected.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Yacoub et al (2018), DAO supplementation was found to be effective in relieving symptoms of urticaria. Recently, the studies by Izquierdo-Casas et al (2019) and Schnedl et al (2019) stated that the supplementation with DAO reduced the duration of migraine attacks and histamine intolerance related symptoms in general, respectively. This is not in accordance with our in vitro results and theoretical conclusions thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Among biogenic amines, histamine is the most likely to cause food poisoning (Izquierdo‐Casas et al . 2019). In this study, high percentages of histamine degradation (over 50%) were detected for sixteen strains, making these good candidates for probiotic use (Table 1).…”
Section: Discussionmentioning
confidence: 99%